Pesan Dakwah Irfan Hakim sebagai MC Hafidz Indonesia - Zuhriyah, Luluk Fikri; Fitria, Alfiana Nur; Adhitama, Tias Satria (Proceedings of International Conference on Da'wa and Communication, 2019)
The issue studied in this paper is how the message of da’wa was delivered by Irfan Hakim in Hafidz Indonesia 2019. The purpose of this study is to know and understand the message of da’wa delivered by Irfan Hakim in Hafidz Indonesia 2019. To identify the problem in depth and thoroughly in this study using qualitative research methods. Then the data obtained through the author's document of analysis using semiotic analysis methods. The results of this study found that the meaning contained in each episode of Hafidz Indonesia 2019 program about the master of ceremony Irfan Hakim there are three kinds of da’wa messages, namely Aqidah, Sharia, and Akhlak. The recommendation in this thesis is so that in the future it can be a reference to the next researcher who wants to review research on the message of da’wa contained in the master of ceremony Irfan Hakim.